2017
DOI: 10.1007/s11747-016-0514-5
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between consumer shopping stress and purchase abandonment in task-oriented and recreation-oriented consumers

Abstract: Shopping is sometimes a source of stress, leading to avoidance coping behavior by consumers. Prior research suggests that store-induced stress makes shopping an adverse experience and thus negatively affects consumers' purchase likelihood. We propose that consumers' response to shopping stress depends on their motivational orientation. The greater the in-store stress, the more likely task-oriented consumers are to abandon the trip without making purchases. However, recreationoriented consumers will be, up to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 68 publications
2
39
1
1
Order By: Relevance
“…Further, participants were asked to read a shopping scenario related to the visuals that manipulated the levels of crowdedness and messiness (see Appendix). The manipulations were adapted from Albrecht, Hattula, and Lehmann (2017).…”
Section: Procedures and Measuresmentioning
confidence: 99%
“…Further, participants were asked to read a shopping scenario related to the visuals that manipulated the levels of crowdedness and messiness (see Appendix). The manipulations were adapted from Albrecht, Hattula, and Lehmann (2017).…”
Section: Procedures and Measuresmentioning
confidence: 99%
“…Regarding passive coping strategies, researchers found that in-store stress can terminate an on-going purchase among task-oriented consumers. However, for recreation-oriented consumers, in-store stress creates an inverted U-shape on purchase abandonment [22]. Regarding active coping strategies, stress enhances both financial savings and spending on necessities [23] because both savings and necessities can compensate for a lack of control.…”
Section: Introductionmentioning
confidence: 99%
“…One major area of research within this theme is shopper behavior. For example, Albrecht et al (2017) investigate how shopping stress negatively affects consumers' purchase likelihood.…”
Section: Marketing Communicationsmentioning
confidence: 99%